An Overview of Natural Inert Dust Utilization Against Stored-Product Pests as Part of Integrated Pest Management: An Overview of Natural Inert Dust Utilization Against Stored-Product Pests - Mario, M. Bayu; Patasik, William Yeremia; Tang, Muh. Ridha Taqwa; Muhammad, Mukhti; Rosyada, Amrina; Jamal, Ahmad Arisandi; Nurwahida; Kafle, Leknath; AM, Samir; Brugman, Eirene; Fernando, Ito (Journal of Tropical Life Science, 2024)
Natural inert dust has been used as a grain protectant since the ancient Aztecs of Mexico to this modern era. Natural inert dust is divided into three groups: the first group includes sand, kaolin, paddy husk ash, wood ash, and clay; the second group includes mineral dust; and the third group includes natural silicas such as diatomaceous earth and zeolite. Natural inert dust has a unique mechanism for killing insect pests. Inert dust particles penetrate the insects’ exoskeleton, causing dehydration through the cuticle. Relative humidity is a crucial factor affecting the efficacy of inert dust application. Inert dust has been traditionally used by farmers, which impacts the insects, such as decreasing population, no insect resistance, and being environmentally friendly. Problems of using inert dust include visible residues on grain, airborne dust, reduced flowability, bulk density reduction, and adverse effects on downstream processing machinery. Moreover, inert dust is a very light product, thus it may cause human respiratory illness. The inert dust can be applied to the smaller or larger storage containers. Natural silica can be readily integrated into modern agriculture as a pest management solution.